Lower adherence to a prudent dietary pattern is associated with earlier age at menarche in adolescents from the Growth and Obesity Chilean Cohort Study - Martínez-Arroyo, Angela; Cantor, Erika; Fisberg, Regina Mara; Corvalán, Camila (Frontiers in Public Health, 2023)
Early menarche is associated with obesity, metabolic and mental health risks, among other diseases. Thus, it is relevant to identify modifiable risk factors of early menarche. Some nutrients and foods advance menarche, but it is unclear how pubertal timing pubertal timing relates to overall dietary patterns. The aim of this study was analyzing the association between dietary patterns and age at menarche in a prospective cohort of Chilean girls of low-middle income families. Survival analysis of 215 girls (median=12.7 years, IQR=12.2-13.2) from the Growth and Obesity Cohort Study (GOCS) who had been followed prospectively since 4y of age (2006). Age at menarche and anthropometric measurements were recorded every 6 months since 7y of age while diet (24HRs) was collected since 11y. Dietary patterns were obtained from exploratory factor analysis. Accelerated Failure Time models adjusted for potential confounding variables were used to study the association between dietary patterns and age at menarche. Girls median age at menarche was 12.7 years. Three dietary patterns were identified: “Breakfast/Light Dinner”, “Prudent” and “Snacking” that explained 19.5% of the diet variation. Girls in the lowest tertile of the “Prudent” pattern had menarche 3 months earlier than girls in the highest tertile (β : 0.022; 95% CI: 0.003; 0.041). “Breakfast/Light Dinner” and “Snacking” patterns were not associated with age at menarche. These results suggest that healthier dietary patterns during puberty might be associated to pubertal timing and, therefore future health. Nevertheless, further studies are required to confirm this result and to clarify the be associated with pubertal timing.